新加坡式华语语气词“Hor”的日常语用功能 = A study on the pragmatics of Singapore colloquial Mandarin particle “Hor” - 邱振毅 Kiew, Zhen Yi (2016)
新加坡及海外学者对于新加坡式英文（Singapore Colloquial English, SCE）中 hor 语用的研究已有许多，但有关于新加坡式华语 hor 的讨论却不多。本文将会带领读者将 hor 在新加坡式华语的语用功能，通过会话分析方式进行分析，探讨hor 在新加坡社会语境的华语日常语用情况下，在话语中产生所产生的作用。透过转写及收集的录像资料，本研究从自然产生的会话语料中，分析新加坡式华语语气词 hor 在日常语用下的功能。并且以社会语言学的视角，去了解新加坡式华语使用者群体，是如何使用 hor 来完成在会话中所要传达的讯息与目的。本文将从过去对于新加坡式英语中，对于 hor 的使用加以探讨，并研究 hor其他对于语用所产生的功能。透过对于 hor 的会话分析，我们发现到 hor 在人与人进行对话引导持续交流是有密切关系的。另外，在一些情况下，本研究也发现 hor能够成为在日常会话中，也是引导说话者应当转移话题的讯号。The SCM Particle, hor is the the focus of this research, which examines how Singapore Chinese uses hor in day to day conversations to achieve various conversational goals. Through an analysis of naturally occurring conversational data, using the Conversation Analysis (CA) method, we seek to explore the use of hor in the Singapore Colloquial Mandarin community, to find out how it affected the interaction between users who utilises “hor” in their conversations, to achieve various conversational goals.Previous analysis on hor had mainly focus upon its use in Singapore Colloquial English (SCE) and thus this research focuses on the use of hor in the Singapore Colloquial Mandarin (SCM), by analysing talks between SCM users. As research on hor in SCM is rather limited, much of our discussion on the function of hor is based on previous researches on the SCE particle hor, as the SCE particle hor is known to have likely the same origins as the SCM hor, thus providing our research with a basis in terms of the pragmatic use of hor in the SCM context, which mostly uses SCE in their daily lives as well. Through this research, it has been discovered that hor could affect the way social interactions are carried out, such as its function in encouraging discussion and talk. In addition, hor is shown to have the effect of a signal to other participants of a talk, when the need for a topic change arises. This study shows how hor can be utilise in various scenarios, to achieve different conversational objectives as shown in the research, by participants in a conversation.